The Oxford illustrated history of the first World War - Strachan, Hew (Oxford University Press, 2014)
The First World War, now a century ago, still shapes the world in which we live. This volume brings together essays by distinguished historians, covering the war's causes and consequences; strategy and tactics; and its political and human legacies